2022
DOI: 10.3389/fpls.2022.905148
|View full text |Cite
|
Sign up to set email alerts
|

OsNAC129 Regulates Seed Development and Plant Growth and Participates in the Brassinosteroid Signaling Pathway

Abstract: Grain size and the endosperm starch content determine grain yield and quality in rice. Although these yield components have been intensively studied, their regulatory mechanisms are still largely unknown. In this study, we show that loss-of-function of OsNAC129, a member of the NAC transcription factor gene family that has its highest expression in the immature seed, greatly increased grain length, grain weight, apparent amylose content (AAC), and plant height. Overexpression of OsNAC129 had the opposite effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Recently, many genes were reported to regulate grain size by participating in multiple phytohormone signaling pathways, such as GA, brassinosteroid (BR), and auxin ( Gao et al 2018 , 2021 ; Duan et al 2020 ; Jin et al 2022 ). GNP1 encodes GA 20-oxidase 1, which promotes cytokinin activity during the dynamic regulation of the KNOX protein, increasing grain number and yield in rice ( Wu et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many genes were reported to regulate grain size by participating in multiple phytohormone signaling pathways, such as GA, brassinosteroid (BR), and auxin ( Gao et al 2018 , 2021 ; Duan et al 2020 ; Jin et al 2022 ). GNP1 encodes GA 20-oxidase 1, which promotes cytokinin activity during the dynamic regulation of the KNOX protein, increasing grain number and yield in rice ( Wu et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic rice overexpressing an OsNAC2 mutant ( OErN ) have better plant architecture and longer panicles, and produce more grains [ 51 ]. In rice, loss of function of OsNAC129 was found to significantly increase grain length, weight, apparent amylose content (AAC), and plant height, while overexpression of OsNAC129 had the opposite effect [ 52 ]. The expression of OsNAC129 was induced by ABA, and overexpression of OsNAC129 in plants reduced sensitivity to exogenous BR, indicating that OsNAC129 negatively regulates seed development and plant growth and participates in the BR signaling pathway.…”
Section: Transcriptional Regulators Pathwaymentioning
confidence: 99%
“…Additionally, loss of function of OsNAC129 was found to significantly increase grain length, weight, apparent amylose content (AAC), and plant height, while overexpression of OsNAC129 had the opposite effect. The expression of OsNAC129 was linked to induced by ABA, and overexpression of OsNAC129 in plants reduced sensitivity to exogenous BR, thereby indicating that overexpression of OsNAC129 negatively regulates seed development and plant growth and participates in the BR signaling pathway ( Jin et al., 2022 ). In addition, studies demonstrated that the DREB-type transcription factor gene GmDREBL is essential for seed oil accumulation ( Zhang et al., 2016b ).…”
Section: Molecular Network Regulating Seed Sizementioning
confidence: 99%